Analisis Future Time Perspective (FTP) dan Kematangan Karir Terhadap Kesiapan Kerja Mahasiswa Sistem Informasi Menghadapi Dunia Kerja Bidang Informatika - Rini Agustina; Yoyok Seby Dwanoko (SMATIKA JURNAL : STIKI Informatika Jurnal, 2021)
One of the triggers for the high rate of intellectual unemployment is due to poor career planning. Lack of skills and competencies makes students find it difficult to choose a career. After completing a higher education program, in many cases, students are not ready to face competition in the world of work, especially in the field of Information Technology which is constantly updated. This study aims to determine the effect of the future time perspective and career maturity of Information Systems Study Program students on their work readiness in the field of informatics. This study uses a quantitative approach, the sample is a student of the Information Systems Study Program with as many as 150 respondents. The measuring instrument used is the Future time perspective (FTP) scale, the Career Maturity Scale, and the Work Readiness scale. Data were analyzed using multiple linear regression and correlation to determine the effect of each variable. The results of the study showed that the influence of the two variables was 38%. The effective contribution of the Future time perspective to Work Readiness is 5%. Meanwhile, the effective contribution of the Career Maturity variable to Work Readiness is 33%. Thus it can be concluded that the Career Maturity variable has a dominant influence on the Job Readiness variable than the Future time perspective variable. Although the contribution of the Future time perspective variable is small, it provides a significant contribution for students because it provides a new discourse in considering their career readiness.